(untitled) (Revista ESASP - Revista Científica Virtual da Escola Superior de Advocacia da OAB/SP, 2025)
This analysis examines the trajectory of global climate governance since Rio-92, highlighting how the choice of Belém for COP-30 symbolizes a paradigmatic transformation towards the leading role of the Global South and the Amazon. (Received: September 2025 | Accepted: November 2025)